Assessing multidisciplinary follow-up pattern efficiency and cost in follow-up care for patients in cervical spondylosis surgery: a non-randomized controlled study - Fu, Zhongmin; Xie, Yan; Li, Peifang; Gao, Menghui; Chen, Jiali; Ning, Ning (Frontiers in Medicine, 2024)
Background The use of multidisciplinary treatment programs in out-of-hospital healthcare is a new area of research. Little is known about the benefits of this method in the management of discharged patients undergoing cervical spondylosis surgery. Objective This study aimed to explore the effect of a contracted-based, multidisciplinary follow-up plan in patients after cervical spondylosis surgery. Methods This non-blinded non-randomized controlled study was conducted with 88 patients (44 in the intervention group, 44 in the control group). The clinical outcomes, including Neck Disability Index (NDI), pain score (VAS), Self-Efficacy for Managing Chronic Disease 6-item Scale (SECD-6), and 12-Item Short-Form Health Survey (SF-12) score were assessed at the time of discharge, 24–72 h, 1 month, and 3 months post-discharge. The complications, patient satisfaction, and economic indicators were assessed at the final follow-up (3 months). Results Patients who received contracted follow-up showed greater improvement in neck dysfunction at 24–72 h, 1 month, and 3 months after discharge compared to those who received routine follow-up (p < 0.001). At 1 month after discharge, the intervention group exhibited better self-efficacy (p = 0.001) and quality of life (p < 0.001) than the control group, and these improvements lasted for 3 months. The intervention group reported lower pain scores at 24–72 h and 1 month (p = 0.008; p = 0.026) compared to the control group. The incidence of complications was significantly lower in the intervention group (11.4%) compared to the control group (40.9%). The total satisfaction score was significant difference between the two groups (p < 0.001). Additionally, the intervention group had lower direct medical costs (p < 0.001), direct non-medical costs (p = 0.035), and total costs (p = 0.04) compared to the control group. However, there was no statistically significant difference in indirect costs between the two groups (p = 0.59). Conclusion A multidisciplinary contract follow-up plan has significant advantages regarding neck disability, self-efficacy, quality of life, postoperative complications, patient satisfaction, and direct costs compared with routine follow-up.